Merry UnChristmas - Reiss, Mike.; Catrow, David (New York : HarperCollins, 2006)
For Noelle and her friends Holly, Carol, and Claus, the most wonderful day of the year is Un-Christmas. It's the only day of the year that they actually go to school. And the mail gets delivered. But the best thing about Un-Christmas Day is that they don't have to open any presents!
Ages 3-7.
1 5 12 13 18 29 33 39
Keywords: Christmas -- Fiction; Stories in rhyme; Christmas -- Juvenile fiction